Estandarización del proceso de obras civiles en el senado de la república (2021)
Public and private organizations are carrying out standardization processes that allow the application of different industrial engineering tools to eliminate activities that don’t add value. In the case of the Senate of the Republic, which is committed to the proper management of the waste generated in civil works and part of the processes of continuous improvement, standardization is proposed based on a diagnosis of the current situation and the search of the procedures that are performed. For the development of the project, we worked a mixed background investigation, since it offers the possibility of generating calculations to express quantifiable results and we performed the description of the data obtained. We gave fulfilment to mentioned items and an analysis of the current situation is made, the documentation is carried out and six quantifiable indicators are proposed. Three procedures are proposed which the necessary formats for the management and final disposal of the waste generated are included, the times are addressed through experts and the impact evaluation is made using the logical framework matrix where the three most important achievements in the development of the project.